ANALISIS DETERMINAN MINAT PENGGUNAAN SI-DOLIR PADA PASIEN BPJS KESEHATAN DI PUSKESMAS I DENPASAR TIMUR - Januraga, Pande Putu; Narendra Suputra, I Dewa Gede Agung (ARCHIVE OF COMMUNITY HEALTH, 2023)
ABSTRACT SI-DOLIR is an online registration offered by Puskesmas I East Denpasar for patients who want to seek routine referral letters so that patients get referral letters more quickly and easily. However, since April-September 2022, the SI-DOLIR target has never been achieved and the program evaluation is inappropriate. The aim of this study was to determine how the effects of UTAUT factors and sociodemographic factors on the intention to use SI-DOLIR using the UTAUT method at Puskesmas I East Denpasar. This research is a cross-sectional design. The sampling technique in this study was consecutive sampling with a sample of 110 respondents. The data will be analyzed using logistic regression analysis. The results of the analysis show that performance expectations, effort expectations, and education level have an influence on their intention to use SI-DOLIR in the future. Meanwhile, social influence, facilitating conditions, age, and gender had no significant effect on interest in using SI-DOLIR in the future when looking for routine referral letters. The conclusion can be drawn if the UTAUT factors of performance expectations and effort expectations as well as the sociodemographic factor of education level affect the interest in using SI-DOLIR for BPJS Health patients to find routine referral letters. Keywords : Intention to Use, Factors, UTAUT, Online Registration